(untitled) (Revista Contexto & Educação, 2024)
Plants are responsible for the survival of most species. Despite this, even with such importance, vegetables are still undervalued in basic education. In a phenomenon described as botanical blindness, plants are barely perceived in a natural environment or in everyday life. In this work, we sought to analyze the manifestations of botanical blindness and the possibilities of overcoming this phenomenon by valuing the knowledge of plant biodiversity. To this end, an activity entitled "Botanical Inventory" was proposed, aimed at the 6° Year of Elementary School and applied in a public school located in the urban area of Santa Maria/RS. To analyze the possible effects of the didactic strategy, pre-test and post-test instruments entitled "Stop Vegetal" were applied. The pre-test mean was 18 species cited, with a standard deviation of 9.68. In the post-test, the mean was 23 species cited and the standard deviation was 12.72. The students showed to recognize a greater number of plant species after the application of the Botanical Inventory, starting to observe more plants in its environment. This result indicates that didactic activities that contextualize botany to the student’s reality can contribute to the reduction of botanical blindness and greater recognition of plant biodiversity.